Palliative Switch: A Surgical Decision After Hybrid Procedure. (January 2014) - Perez-Negueruela, Carolina; Mayol, Javier; Cesar, Sergi; Muchart, Jordi; Segura, Susana; Caffarena-Calvar, Jose Maria
The first-stage palliation of newborns with single-ventricle anatomy and transposed great arteries can be very challenging when associated with systemic ventricular outflow obstruction and aortic arch obstruction. Often, the initial intervention is a stage I Norwood procedure. We present the case of a newborn with double inlet left ventricle, discordant ventriculoarterial connection with restrictive ventricular foramen, and severe aortic arch obstruction. A hybrid procedure was performed initially as a means of addressing hemodynamic instability. Three months later, a palliative arterial switch procedure was performed as an alternative to the combined Norwood-Glenn procedure. Palliative arterial switch combined with arch reconstruction can be an effective surgical option in these complex, challenging patients.